The Effect of ICT on the Development of Bank Branches in the WAEMU Zone: An Application of Negative Binomial Regression - Yao Séraphin, PRAO; Tanmantchin Brice-Wilfried, OUATTARA (International Journal of Accounting and Financial Reporting, 2024)
The main objective of this study is to analyze the effect of ICT on the number of bank branches in the WAEMU. Based on the total of eight (08) member countries of the union, from 1995 to 2022, it employs the negative binomial (BN) regression method for the estimations. The results of the study show that among the ICT variables selected, only mobile and fixed-line telephone subscriptions have a statistically significant and positive effect on the number of bank branches in the union. The Internet and the number of ATMs have no significant effect on the number of branches, although they remain negatively correlated with the number of bank branches. On the other hand, the number of banking institutions and the size of these banks encourage the opening of new bank branches.